2015
DOI: 10.1039/c4cp04769a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of negative pressure aging on the aggregation of Cu2O nanoparticles and its application to laser induced copper electrode fabrication

Abstract: The aggregation and dispersion of nanoparticles are critical problems in selective laser sintering. In this study, negative pressure aging was applied to resolve the aggregation of nanoparticles and a metal oxide reduction method used to make a well-dispersed nanoparticles in solvent. As a result, metal oxide nanoparticles were synthesized according to a grade of the aggregation and aging conditions found to provide well-dispersed nanoparticles in solvent with less re-dissolution of the nanoparticles. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
8
0
1
Order By: Relevance
“…This phenomenon suggests that the formation of diverse morphologies is influenced by the selective adsorption of capping agents onto specific crystal surfaces. [32][33][34] The capping agent, generated in an alkaline environment with a pH range of 7 to 13, is introduced into the system during particle development. The injected capping agent molecules tend to adsorb onto higher energy planes preferentially.…”
Section: Methodsmentioning
confidence: 99%
“…This phenomenon suggests that the formation of diverse morphologies is influenced by the selective adsorption of capping agents onto specific crystal surfaces. [32][33][34] The capping agent, generated in an alkaline environment with a pH range of 7 to 13, is introduced into the system during particle development. The injected capping agent molecules tend to adsorb onto higher energy planes preferentially.…”
Section: Methodsmentioning
confidence: 99%
“…However, the organic carriers are usually a long chain polymerization whose thermal decomposition temperature is above 250 °C [ 109 ]. Notably, Lee et al found that besides the dispersant, negative pressure aging can also effectively solve the aggregation of nanoparticles, which will promote the sintering process of nanoparticles [ 110 ].…”
Section: Preparation Of Nanosilver Particles and Pastesmentioning
confidence: 99%
“…The ink used in LDW is mainly the nanoparticles of metal or nonmetal with low cost. The nano metal oxide inks in non-metallic ink include nano NiO [ 9 ], nano CuO [ 10 , 11 ], nano Cu 2 O [ 12 ], and so on. Among them, the nano CuO ink, which can be reduced and sintered into a Cu electrode pattern by laser in the preparation of a flexible circuit [ 13 ], is a focus researched ink.…”
Section: Introductionmentioning
confidence: 99%